Pengaruh Talent Management, Work Life Balance, dan Budaya Organisasi Terhadap Kinerja Karyawan Departemen HRGA PT Bumi Suksesindo Banyuwangi - Antika Yashifa Tito Putri; Prajitiasari, Ema Desia; Susanto, Arnis Budi; Andriana; Kurniaty; Afandi, Mochammad Farid (VALUE: Journal of Business Studies, 2025)
The objective of this research is to analyze the influence of talent management, work life balance, and organizational culture on employees’ performance in the HRGA Department at PT Bumi Suksesindo Banyuwangi. This study is classified as explanatory research, using quantitative data obtained through questionnaires and literature review. The research sample was selected using the total sampling method, meaning that the entire population of 72 employees in the HRGA Department at PT BSI Banyuwangi was included as the research sample. The data analysis method used was the multiple linear regression with the assistance of IBM SPSS Statistics software. The research finding reveals that talent management, work life balance, and organizational culture have a partially significant impact on employees’ performance in the HRGA Department at PT Bumi Suksesindo Banyuwangi.